1995
DOI: 10.1080/0950069950170204
|View full text |Cite
|
Sign up to set email alerts
|

A classroom intervention using a computer‐augmented curriculum for mechanics

Abstract: A set of teaching materials was developed for the teaching of mechanics, as part of the research carried out for the 'Conceptual Change in Science' project. These incorporated a series of interactive computer simulations, associated written materials and a number of practical activities; their aim was to promote change in learners' conceptual understandings of natural physical phenomena. The materials were described in the preceding issue of this journal . This paper presents the results of an empirical evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 7 publications
1
8
0
3
Order By: Relevance
“…In keeping with our prior research (Hennessy et al, 1995), it seems that deliberate use of simulations employing real-world scenarios that visually challenge common everyday beliefs and hence create conceptual conflict, and using those that persist as teaching points during discussion with pupils, can be quite successful in helping both to identify learning demands (Leach & Scott, 2004) and to move children's thinking on towards a more scientific model.…”
Section: Attending To Pupils' Everyday Conceptionssupporting
confidence: 63%
See 1 more Smart Citation
“…In keeping with our prior research (Hennessy et al, 1995), it seems that deliberate use of simulations employing real-world scenarios that visually challenge common everyday beliefs and hence create conceptual conflict, and using those that persist as teaching points during discussion with pupils, can be quite successful in helping both to identify learning demands (Leach & Scott, 2004) and to move children's thinking on towards a more scientific model.…”
Section: Attending To Pupils' Everyday Conceptionssupporting
confidence: 63%
“…Handling a physical model or employing visual aids can enhance learning during simulationsupported activity; our previous interviews with science and technology teachers indicated that "hands-on" experiences are highly valued . Moreover, rather than using the technology in isolation, the products of simulation-based activity can be explicitly linked with other class activities before, during, and after the computer-based lesson (Finlayson & Rogers, 2003;Hennessy et al, 1995). This means that practical demonstration and development of pupils' investigative skills retain some importance.…”
Section: Linking Simulation Use Theory and Practical Workmentioning
confidence: 99%
“…Computer-based modeling environments, suited to a variety of kinds of student, have been developed. Examples of evidence of effectiveness of use of computer models include Weaver (2000) and Hennessy et al (1995).…”
Section: Modeling and Simulationmentioning
confidence: 99%
“…Knowledge construction is assisted by exploring experiments in a simulation of the real world. At the same time, experiential learning promotes a 'direct encounter' with the phenomena being studied rather than merely thinking about them [6], [9], [10].…”
Section: B Pedagogical Requirementsmentioning
confidence: 99%